Safety learning during adolescence facilitates fear regulation in adult mice - Heidi C. Meyer (Developmental Cognitive Neuroscience)
Experiences during sensitive early life developmental periods such as adolescence have a profound influence on brain maturation and long-term affective behavior. While substantial work focuses on early life adversity, emerging evidence suggests that positive affective experiences can also shape trajectories of neurobehavioral development. This study examined how experience with fear conditioning or discriminative conditioning (i.e., safety learning) during either adolescence or adulthood in male and female mice influenced fear behavior and engagement with an anxiogenic environment one month later, when adolescents had aged to adulthood. Prior conditioning (both fear and safety training) at either age, regardless of valence, promoted later fear generalization to a novel cue. In contrast, safety learning during adolescence conferred enduring benefits, leading to reduced fear expression and enhanced extinction memory in adulthood, whereas similar training in adulthood offered limited protective effects. Behavior in the elevated plus maze revealed increased movement in all previously conditioned animals (both Fear-trained and Safety-trained groups), with safety learning decreasing initial freezing in the maze and accelerating initial re-location from the placement arm. Sex differences in this study were modest, showing limited interaction with age and minimal impact on training-related outcomes across experimental phases, suggesting that the effects of conditioning on later affective regulation are robust and broadly conserved across sexes. Overall, these findings highlight adolescence as a sensitive period during which safety learning can shape affective regulation and potentially buffer against later life pathological fear responding. This work offers insight into developmental mechanisms that may inform early interventions for psychiatric conditions like anxiety.